STRATEGI PEMBELAJARAN PENDIDIKAN LUAR SEKOLAH - Bertha Bintari Wahyujati (Jurnal Ilmiah Visi, 2006)
Instructional strategy is one of important factors to achieve instructional objectives. The instructional strategy developed for a teaching and learning situation will be effective if instructional methods and models are appropriately selected. This article discusses some considerations upon the selection of appopriate instructional strategies and describes a case study in life skills training. The case proves the significant role of appropriate instructional strategies in achieving training objectives.